Respuesta :
Answer:
see explanation
Step-by-step explanation:
to evaluate f(g(x)) substitute x = g(x) into f(x), that is
f(g(x)) = f(x - 1) = 3(x - 1) = 3x - 3
Similarly to evaluate g(f(x)) substitute x = f(x) into g(x)
g(f(x)) = g(3x) = 3x - 1
Answer:
(f∘g)(x) = f(g(x)) = 3x - 3
(g∘f)(x) = g(f(x)) = 3x - 1
Step-by-step explanation:
The question should read
f(x) = 3x
g(x) =x-1
find (f∘g)(x) and (g∘f)(x)
∘ is U+2218 RING OPERATOR
In this case it is read "composed with".
To find (f∘g)(x) = f(g(x)), substitute g(x) for x in formula for f(x). Then substitute the formula for g(x).
(f∘g)(x) = f(g(x)) = 3(g(x)) = 3(x-1) = 3x-3
(g∘f)(x) = g(f(x)) = f(x) - 1 = 3x - 1